Fertilization reduces aphid population growth but does not alter competitive exclusion between specialist and generalist species - Ayako Nakatani; Fumika Shindoh; Tatsuya Saga (PLoS ONE, 2025)
Understanding how resource availability shapes herbivore competitive interactions is crucial for predicting pest dynamics under changing agricultural practices. Interspecific competition among herbivorous insects is mediated by host plant quality, yet mechanisms underlying competitive outcomes under varying nutrient conditions remain unclear. We investigated how fertilization with a liquid N–P–K (5:8:12.5) solution diluted to 0.2% (v/v) affects population dynamics and competitive interactions between the legume-specialist Megoura crassicauda and the generalist Aphis craccivora on pea shoots ( Pisum sativum ) under fertilized and unfertilized conditions. Aphid population dynamics were monitored for 30 days in single-species and mixed-species treatments, and plant survival and biomass changes were assessed as whole-plant indicators of host performance under herbivory. Under single-species conditions, fertilization reduced M. crassicauda population growth (peak population decreased from 77.2 ± 28.6 to 50.7 ± 25.2 individuals per plant), while effects on A. craccivora were more modest (from 187.1 ± 48.0 to 141.6 ± 43.0). Area-under-the-curve analysis and peak abundance differed between species and were generally lower under fertilization. In mixed cultures, A. craccivora consistently dominated; M. crassicauda was excluded by day 25 under both nutrient regimes. Plants without aphids all survived, whereas mortality occurred in every aphid treatment except M. crassicauda with fertilization, indicating shorter survival times in aphid treatments than in controls. These results show that nutrient enrichment unexpectedly depressed herbivore population growth and did not relax interspecific competition. Competitive hierarchy was stable across nutrient regimes, with the generalist excluding the specialist.